Bottom-up or Direct? Forecasting German GDP in a Data-rich Environment - Katja Drechsel; Rolf Scheufele (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2013)
This paper presents a method to conduct early estimates of GDP growth in Germany. We employ MIDAS regressions to circumvent the mixed frequency problem and use pooling techniques to summarize efficiently the information content of the various indicators. More specifically, we investigate whether it is better to disaggregate GDP (either via total value added of each sector or by the expenditure side) or whether a direct approach is more appropriate when it comes to forecasting GDP growth. Our approach combines a large set of monthly and quarterly coincident and leading indicators and takes into account the respective publication delay. In a simulated out-ofsample experiment we evaluate the different modelling strategies conditional on the given state of information and depending on the model averaging technique. The proposed approach is computationally simple and can be easily implemented as a nowcasting tool. Finally, this method also allows retracing the driving forces of the forecast and hence enables the interpretability of the forecast outcome. – – Dieser Beitrag diskutiert eine Methode, frühzeitig die Wachstumsrate des deutschen Bruttoinlandsproduktes des laufenden Quartals zu bestimmen. Es werden MIDASRegressionen verwendet, um mit dem Problem unterschiedlicher Datenfrequenzen umzugehen. Zudem werden Pooling-Ansätze diskutiert, die den Informationsgehalt verschiedener Indikatoren effizient zusammenzufassen. Im Folgenden wird untersucht, ob es besser ist, das BIP zu disaggregieren (entweder über die Entstehungsseite oder über die Verwendungsseite) oder ob ein direkter Ansatz besser geeignet ist, das BIPWachstum zu prognostizieren. Das hier besprochene Vorgehen vereint eine große Anzahl von monatlichen und vierteljährlichen Indikatoren unter Berücksichtigtigung ihrer jeweiligen Veröffentlichungstermine. In einem simulierten Out-of-Sample-Experiment werden die verschiedenen Modellierungsstrategien bei unterschiedlichem Dateninformationsstand und je nach Prognosekombinationstechnik verglichen. Der vorgeschlagene Ansatz lässt sich leicht praktisch implementieren und kann als Prognosetool genutzt werden. Schließlich ermöglicht diese Methode sehr transparent, die treibenden Kräfte der Prognose nachzuvollziehen und ermöglicht somit die Interpretierbarkeit des Prognoseergebnisses.
urn:nbn:de:gbv:3:2-22469
Keywords: E32; E37; C52; C53; 330; Contemporaneous aggregation; nowcasting; leading indicators; MIDAS; forecast combination; forecast evaluation; Kontemporäre Aggregation; Nowcasting; Frühindikatoren; MIDAS; Prognosekombination; Prognoseevaluation